Clinical relevance of endoscopically identified extrinsic compression of the oesophagus and stomach. Issue 1 (17th July 2019) - Kumar, Kishore; Patel, Harish; Mehershahi, Shehriyar; Tariq, Hassan; Glandt, Mariela; Erfani, Mohamad; Dev, Anil; Zhang, Aiyi; Makker, Jasbir
Abstract : Background: Various degree of extrinsic compression of the oesophagus and stomach are experienced during upper endoscopy. However, its utility in clinical practice has not been studied. Methods: Electronic chart review of all upper gastrointestinal endoscopies done at our hospital between 2005 and 2016 was performed. A total of 79 patients with documented extrinsic compression on upper gastrointestinal procedure report who had a preceding or subsequent abdomen/chest CT imaging performed within 6 months were included. Results: 30 (38%) out of 79 patients had abnormal finding on CT scan. 14 (47%) out of 30 patients had an associated malignant lesion, whereas remaining had a benign lesion. Overall, patients with associated gastrointestinal symptoms (60% vs 22%, p=0.001) or history of weight loss (50% vs 16%, p=0.001) had increased odds of having an abnormal finding on CT scan compared with the patients who lacked such symptoms. Pancreatic cancer was the most commonly diagnosed malignancy. On subgroup analysis of patients with extrinsic compression and malignant lesion on imaging study, the likelihood of a malignancy was higher in blacks as compared with Hispanics (71%:29% vs 39%:61%, p=0.031), and with presence of gastrointestinal symptoms (64% vs 22%, p=0.003), presence of weight loss (64% vs 16%, p=0.0001) and hypoalbuminaemia (p=0.001). Conclusion: Finding an extrinsic compression of the oesophagus and stomach on an upper endoscopy may suggest malignancy, and hence should prompt further work-up. Posterior wall gastric body compression may signal the presence of pancreatic cancer.